Pengaruh Model Pembelajaran Kooperatif Tipe STAD (Student Team Achievment Division) Terhadap Keterampilan Passing Sepakbola - Ridha Hartono Kadry; Abdul Salam Hidayat; Muhammad Arief Setiawan (Jurnal Literasi Olahraga, 2021)
The purpose of this rasearch is the formulation of the problem above, namely: to determine the effect of the stad type cooperative learning model (student team achievment division) on the basic technical skills of foodball passing in class XI IPS 1 students at MAN 2 karawang. The sample in this study was aut of 10 classes as the population in MAN 2 karawang, as many as 30 students. Divide into two, 15 people in the treatment group and 15 people in the control group. From the results of the research and discussion, it can be concluded that the stad type cooperative learning model (sudent team achievement) has an influence on basic football passing technique skilles in class XI 1MAN 2 karawang. Keywords : learning model, basic football passing thecnique skills.